Triangular ratio metric in the unit disk - Rainio Oona; Vuorinen Matti (Taylor & Francis Ltd, 2022)
The triangular ratio metric is studied in a domain G subset of Rn, n >= 2. Several sharp bounds are proven for this metric, especially in the case where the domain is the unit disk of the complex plane. The results are applied to study the Holder continuity of quasiconformal mappings.